PENGARUH STRES KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION DI SIMPANG INN HOTEL KUTA - Udayana, I Gusti Agung Praditya; Dewi, I Gusti Ayu Manuati (E-Jurnal Manajemen; Vol 6 No 12 (2017), 2017)
The purpose of this study is to determine the effect of work stress and organizational commitment to turnover intention employees at Simpang Inn Hotel Kuta. Turnover intention is a reflection of low employee loyalty to the company caused by several things, one of which is high work stress. Turnover intention will affect the performance and sustainability of the company. This research was conducted on the employees of Simpang Inn Hotel with a sample of 50 employees. The sampling technique is saturated sampling. The analysis technique used is Multiple Linier Regression. The results showed that first, work stress had a positive and significant effect on turnover intention. Second, organizational commitment has a negative and significant effect on turnover intention. To reduce work stress, then the management needs to add employees to lighten the burden of other employees. In addition to lowering stress, organizational commitment support becomes a strong benchmark for reducing turnover intention. In this case it is suggested the Simpang Inn Kuta Hotel care about the opinions expressed by the rich and appreciate every effort made.   Keywords: job stress, organizational commitment, turnover intention.